THE CONCEPT OF CRIME COMMITMENT REGULATIONS IN THE INDUSTRIAL WASTE OF PLANTATION COMPANIES - Marvel Romi Sutiono (LPPM Universitas Ekasakti Padang, 2023)
The issue of industrial waste in the plantation industry has become an urgent concern in efforts to maintain environmental sustainability. This research aims to analyze the policy strategies for combating crimes related to industrial waste in plantation companies. The implementation of policies for managing and addressing crimes related to industrial waste in plantation companies is a crucial factor in mitigating the environmental problems caused by plantation activities. The research methodology employed is normative legal research, which involves analyzing various legal regulations through literature review and normative analysis. This study identifies the legal principles that should form the basis of policies for combating crimes related to industrial waste in the plantation industry. Additionally, the research identifies weaknesses in existing policies and provides recommendations for new strategies that can be implemented, such as strengthening surveillance and law enforcement, active participation of companies and communities, and the adoption of environmentally friendly technologies. This research is expected to contribute to the formulation of more effective policies for combating crimes related to industrial waste in the plantation industry. The research identifies factors influencing policy implementation, such as the awareness and active participation of companies, the role of the government in surveillance and law enforcement, and the involvement of the community in monitoring and reporting violations. The research findings provide an overview of the challenges and obstacles faced in policy implementation and offer recommendations to enhance the effectiveness of implementation in optimizing the management of combating crimes related to industrial waste in plantation companies.